Multimodal physiotherapy is effective for anterior knee pain relief - Oliveira, Vinicius Cunha; Henschke, Nicholas (British journal of sports medicine, 2013)
This section features a recent systematic review that is indexed on PEDro, the Physiotherapy Evidence Database (www.pedro.org.au). PEDro is a free, web-based database of evidence relevant to physiotherapy. - Anterior knee pain is a prevalent musculoskeletal condition which often has a poor prognosis and can significantly impact daily activities as well as participation in physical activity. Management of anterior knee pain involves consideration of each individual's presentation and the potential contribution of local (eg, patellar alignment and quadriceps strength), proximal (eg, hip) and distal (eg, foot) knee factors.1 Non-surgical interventions appear to be the primary treatment of choice for anterior knee pain;2 however, evidence to support these interventions is currently inconclusive. - The aim of the systematic review was to evaluate the short-term and long-term efficacy of non-surgical interventions for anterior knee pain. - Nine databases (ie, MEDLINE, EMBASE, CINAHL and PRE-CINAHL, PEDro, PubMed, SportDiscus, Web of Science, BIOSOS Previews and the full Cochrane library) were searched up to November 2009 for randomised controlled trials published in English. Trials were eligible if they investigated at least one non-surgical intervention for anterior knee pain compared with a control group with a follow-up of …